Androgen-Regulated Cardiac Metabolism in Aging Men - Barrientos, Genaro; Llanos, Paola; Basualto-Alarcón, Carla; Estrada, Manuel (Frontiers in Endocrinology, 2020)
The prevalence of cardiovascular mortality is higher in men than in age-matched premenopausal women. Gender differences are linked to circulating sex-related steroid hormone levels and their cardio-specific actions, which are critical factors involved in the prevalence and features of age-associated cardiovascular disease. In women, estrogens have been described as cardioprotective agents, while in men, testosterone is the main sex steroid hormone. The effects of testosterone as a metabolic regulator and cardioprotective agent in aging men are poorly understood. With advancing age, testosterone levels gradually decrease in men, an effect associated with increasing fat mass, decrease in lean body mass, dyslipidemia, insulin resistance and adjustment in energy substrate metabolism. Aging is associated with a decline in metabolism, characterized by modifications in cardiac function, excitation-contraction coupling, and lower efficacy to generate energy. Testosterone deficiency -as found in elderly men- rapidly becomes an epidemic condition, associated with prominent cardiometabolic disorders. Therefore, it is highly probable that senior men showing low testosterone levels will display symptoms of androgen deficiency, presenting an unfavorable metabolic profile and increased cardiovascular risk. Moreover, recent reports establish that testosterone replacement improves cardiomyocyte bioenergetics, increases glucose metabolism and reduces insulin resistance in elderly men. Thus, testosterone-related metabolic signaling and gene expression may constitute relevant therapeutic target for preventing, or treating, age- and gender-related cardiometabolic diseases in men. Here, we will discuss the impact of current evidence showing how cardiac metabolism is regulated by androgen levels in aging men.